Pengaruh Media Puzzle Terhadap Pengetahuan Jajanan Sehat Pada Siswa Di Sekolah Dasar - Putri, Tania Sinika; Muharramah, Alifiyanti; Junita, Dera ELva; Wati, Desti Ambar (Media Gizi Ilmiah Indonesia, 2024)
Child nutrition is a worldwide concern. One of the causes of nutritional problems in school-age children is the selection of snacks consumed. Snacking behavior is closely related to their knowledge about healthy snacks. One of the efforts that can be done to improve knowledge is to provide education with educational media in the form of puzzles. The purpose of this study was to determine the effect of using puzzle media on school children's knowledge about healthy snacks at SD Negeri 5 Bumi Nabung Ilir. This research is a quantitative analytic research with pretest-posttest control group design. The subjects in this study amounted to 62 elementary school children who were divided into an intervention group of 31 children and a control group of 31 children. The intervention group was the group that received education using puzzle media and the control group was the group that received education without puzzle media. Knowledge about healthy snacks was assessed before and after the study which was seen based on the analysis score using the Wilcoxon Test and the Mann-Whitney Test. The results showed that the average knowledge of children before the intervention in the control group increased by 3.13 points while in the intervention group it increased by 4.4 points. There is a difference in knowledge scores about healthy snacks in children at SD Negeri 5 Bumi Nabung Ilir (p= 0.000). The study conclusion is that nutrition education with puzzle media can increase knowledge in school children about healthy snacks